Optimizing Broiler Production Capacity Through Master Production Schedule (MPS) and Rough Cut Capacity Planning (RCCP) at PT X - Muhammad Rizki Abdullah; Reiny Myrtanti; Ellysa Nursanti (JURNAL REKAYASA SISTEM INDUSTRI, 2026)
Fluctuations in market demand for broiler chickens pose a challenge for broiler processing companies in balancing demand with production capacity. PT X often faces problems with actual capacity mismatch with production schedules, potentially causing delays or stock shortages. This study aims to optimize broiler production capacity at PT X through the implementation of Master Production Schedule (MPS) and Rough Cut Capacity Planning (RCCP). The research method used is a quantitative approach by collecting and analyzing data on production, demand, inventory, and safety stock levels. The MPS is prepared to determine the amount of production needed in a certain period based on projected demand and inventory conditions. Furthermore, RCCP is applied as an evaluation stage to assess the suitability of available production capacity with MPS needs. From the preparation of the MPS scheduled weekly, the results obtained were 221,944 kg / week, then from the analysis with RCCP through the Bill of Labor approach, it was found that several work centers showed a capacity shortage compared to MPS needs, especially at work center I which uses a drum chiller machine. The recommended improvement proposal is to add 1-2 hours of overtime per shift to close the production capacity gap. The research results show that the implementation of MPS can provide a more structured overview of the production schedule, while RCCP plays a crucial role in ensuring existing production capacity can meet demand needs. Thus, the combination of MPS and RCCP supports company decision-making and optimizes production capacity planning at PT X.